Social Factors Affecting Elective Cesarean in Iran: social factors affecting to elective cesarean - Tavassoli , Afsaneh; Zafari Dizaji , Ashraf (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Cesarean section is a type of delivery, which has recently attracted the interest of numerous pregnant women. According to the general principles of medical ethics, to respect the individuals’ right to independence, the medical staff must provide the patients with the necessary information to enable them to involve in the decision-making process freely and informedly. In addition, the medical staff must adhere to the rule of “evaluation of risks and benefits” in the treatment process. This rule should be also applied in the selection of delivery methods for pregnant women. The present study aimed to evaluate the social factors affecting the tendency of pregnant women toward an elective cesarean section in the past few years. Materials and Methods: This descriptive-analytical study was conducted on 200 women in the third trimester of pregnancy referring to the hospitals located in the District one of Tehran, Iran. The data were collected using a researcher-made questionnaire. Data analysis was performed using descriptive and inferential statistics. Ethical Considerations: After the explanation of the study objectives, written informed consent was obtained from all participants. Findings: According to the results, elective cesarean delivery showed a significant relationship with maternal awareness of cesarean birth complications, encouragement by physicians, fear of normal delivery, imitation of others, maintenance of the body beauty, social and economic status, maternal occupation, family income, and parental occupation. However, the elective cesarean section had no significant association with awareness about the benefits of vaginal birth and decreased maternal role. Conclusion: Although pregnancy and delivery are physiological phenomena, they are regarded as a “disease” in modern medicine. Moreover, gynecologists have prevented the women from consciously deciding about their own choice of delivery. The encouragement of the mothers to undergo cesarean section by the specialists, along with the women’s attitudes about vaginal delivery, has led to the enhanced use of cesarean birth in Iran. The women’s higher awareness about the benefits of normal delivery and cesarean section complications assisted them in making a better choice about their delivery method. *Corresponding Author: Ashraf Zafari Dizaji; Email: az9405@gmail.com; ORCID: https://orcid.org/0000-0002-5357-1785 Please cite this article as: Tavassoli A, Zafari Dizaji A. Social Factors Affecting Elective Cesarean in Iran. Bioeth Health Law J. 2021; 1:1-7 (e24). http://doi.org/10.22037/bhl.v1i1.38186